(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
Fluorescent Pseudomonas isolated from oil-spilled soil were studied for the degradation of oil (Commercially available 2T oil) sample by growing in Bushnell Hass medium. The hydrocarbon degradation was measured calorimetrically in the basal media based on the turbidity. The degraded oil sample was utilized for studying its efficiency in Phaseolus aureus seeds germination. The thin layer chromatographic technique differentiates the specific components of antifungal metabolites and was isolated by centrifugation technique showed the Rf value of about 0.34. Antagonistic potential of these metabolites were demonstrated by agar diffusion method and spot inoculation method. The present study thus demonstrated the ability of the isolated Pseudomanas fluorescens to utilize crude oil in liquid media and to compete with indigenous soil microorganisms, enhance crude oil degradation and reduces its phytotoxicity. Key words: Biodegradation; Petroleum hydrocarbons; Pseudomanas fluorescens; Phytopathogen; Antifungal activity DOI: http://dx.doi.org/10.3329/bjsir.v46i3.3858 BJSIR 2011; 46(3): 297-302